STATUS UNSUR HARA Ca, Mg DAN S SEBAGAI DASAR PEMUPUKAN TANAMAN KEDELAI (Glycine max L. Merril) DI KECAMATAN PUNUNG KABUPATEN PACITAN - Supriyadi Supriyadi; Sri Hartati; Endro Yunianto (Sains Tanah - Jurnal Ilmu Tanah dan Agroklimatologi, 2011)
Title : The Status of Ca Mg and S Nutrient as Basic Fertilizing of Soybean (Glycine max L. Merril) in Punung, Pacitan. The purpose of this research was to recognize the availability of Calcium (Ca) Magnesium (Mg) and Sulphur (S) nutrient, to give fertilizing suggestion, to give common fertilizing and soil management strategy. This research was phenomenological Descriptive Qualitative research by means of field survey which supported with soil analysis in lab. The determining of Ca Mg and S nutrient status and its management strategies was checked on each land units. The land unit’s map in Punung was obtained by overlaid soil map, slope map and land use map. From the overlay was obtained 19 land units. At the time that, The soil sampling take out in each land unit was doing as randomize (purposive sampling), to calculated the necessity of fertilizer based on the difference number of nutrient available in the soil and total removal Glycine max L. merril nutrient with the number of nutrient that carry on (total removal) in the harvest time, at the time that to determine fertilizing suggestion based on the result of fertilizer necessity (surplus or deficit) each unit land (SPL). Punung fertility level in common based on the Ca nutrient status are medium (6.08-7.87 cmol/kg), Mg nutrient status are high (4.05-5.25 cmol/kg) and S nutrient status are very low ((0.0013-0.0001%). The fertility suggestion was directed to the needed of S nutrient by adding the inorganic fertilizer that is ZA and Phonska. The rights soil and plant management strategies in Punung are: (1) Fertilizing of organic fertilizer as big as 5 ton/ha. (2) In the slope area by making level to the land as an effort to reduce erosion level. (3) In the flat area by using and making the mulch and the drainage line. (4) The right management plants by rotation system and planting in the same direction of contour line. Keywords: Glycine max L. Merril, nutrient status, soil management